Narasi Bias Gender Dalam Tafsir Nusantara - Mamluatun Nafisah (Al-Fanar: Jurnal Ilmu Al-Qur’an dan Tafsir, 2023)
This paper departs from the interpretation of couples in heaven who are considered less friendly to women's groups. This paper discusses how the Nusantara interpreters interpret zauj as a partner in heaven. There are five books of interpretation chosen in this paper, namely Tafsir Marah Labid, Tafsir Al-Ibriz, Tafsir an-Nur, Tafsir Al-Azhar, and Tafsir Al-Misbah. To find out their views on the meaning of zauj as a partner in heaven, the author uses a historical approach. The results of this study conclude that the interpretation of Quraish Shihab in Tafsir Al-Misbah on the word zauj as a partner in heaven is much more gender-friendly than the previous commentators. If mapped, Nawawi al-Bantani, Bisri Musthofa, Hamka and Hasbi tend to follow the current view of the traditional commentators.